The Addition of Zinc in Nutritive Rich Feed Containing Lemuru Oil to Growth and Birth Weight of Bali Cattle - Hartati, E; Katipana, NGF; Saleh, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
An experiment was conducted to examine the addition of zinc in nutritive rich feed contained lemuru oil to growth and birth weight of Bali cattle. The experiment design used was randomized complete block design. The animal were randomly assigned into four group of treatments, i. e addition of 0, 75, 150 and 225 mg ZnSO4 kg-1 on nutritive rich feed (NRF) containing lemuru oil. The basal diet consist dried grass while NRF consisted of palm sugar, leucaena and glirisidia leaf meal, rice bran fermentation, fish meal, lemuru oil and urea. The crude protein content of NRF was 23%, while total digestible nutrient (TDN) was 70%. Addition ZnSO4 in the diet did not increase significantly zinc status, prostaglandin E2 (PGE2) concentration and ME retention. However, level of ZnSO4 addition increase significantly (P<0.01) zinc absorption, N retention, growth and birth weight of Bali Cattle (P<0.01). The fastest of growth was achieved at level of ZnSO4 addition of 150 mg ZnSO4.kg-1 NRF. (Animal Production 11(1): 59-65 (2009) Key Words: Bali cattle, PGE2, zinc absorption, growth